Can the ACS‐NSQIP surgical risk calculator predict postoperative complications in patients undergoing sacral tumor resection for chordoma?. Issue 6 (7th February 2020) - Houdek, Matthew T.; Hevesi, Mario; Griffin, Anthony M.; Yaszemski, Michael J.; Sim, Franklin H.; Ferguson, Peter C.; Rose, Peter S.; Wunder, Jay S.
Abstract: Background and Objectives: The ACS‐NSQIP surgical risk calculator is an online tool that estimates the risk of postoperative complications. Sacrectomies for chordoma are associated with a high rate of complications. This study was to determine if the ACS‐NSQIP calculator can predict postoperative complications following sacrectomy. Methods: Sixty‐five (42 male, 23 female) patients who underwent sacrectomy were analyzed using the Current Procedural Terminology (CPT) codes: 49215 (excision of presacral/sacral tumor), 63001 (laminectomy of sacral vertebrae), 63728 (laminectomy for biopsy/excision of sacral neoplasm) and 63307 (sacral vertebral corpectomy for intraspinal lesion). The predicted rates of complications were compared to the observed rates. Results: Complications were noted in 44 (68%) patients. Of the risk factors available to input to the ACS‐NSQIP calculator, tobacco use (OR, 20.4; P  < .001) was predictive of complications. The predicted risk of complications based off the CPT codes were: 49215 (16%); 63011 (6%); 63278 (11%) and 63307 (15%). Based on ROC curves, the use of the ACS‐NSQIP score were poor predictors of complications (49215, AUC 0.65); (63011, AUC 0.66); (63307, AUC 0.67); (63278, AUC 0.64). Conclusion: The ACS‐NSQIP calculator was a poor predictor of complications and was marginally better than a coin flip in its ability to predict complications following sacrectomy for chordoma.